Plain Tiger Butterfly (Danaus chrysippus) Lepidopterarium, As a Bio-entrepreneurship Model: Bio-entrepreneurship Model of Butterfly (Biological Sciences - PJSIR, 2025)
The integration of bio-sciences and business is known as bio-entrepreneurship. It is the transfer of innovation from academy to business. A good bio-entrepreneur applies scientific methods to launch a business. This study explored bio-entrepreneurship opportunities in the field of biology, with the plain tiger butterfly as a representative business model. The Lepidopterarium breeds and displays butterflies while educating visitors. To grow Lepidopterarium, bio-entrepreneur must have some knowledge about butterflies. Butterflies have emerged as a critical player in addressing environmental challenges by serving as an indispensable climate indicator. In bio-entrepreneurship model the butterfly effect as a “real business model” rather than just a butterfly effect only in which life cycle of plain tiger butterfly as the representative. Every step of butterfly’s life cycle is essential for different industries e.g., climate research labs, educational institutions, recreational tools, decor industries, tourism and even for the rituals.